Incidencia del agua de servicio público en la salud de los estudiantes de la Unidad Educativa Vinces Provincia de Los Ríos - Rosado Arana, Miguel Ángel (2019)
The only substance essential for life that appears in the three possible states of matter, solid, liquid and gaseous is water, and it also occurs in the most superficial portion of the soil, where particles, by capillary action, adhere of the same. Due to the influence of gravity, water accumulates in the interstices present both in the rocks and between them, below the earth's surface and forming underground water deposits that supply wells and springs, and maintain the flow of some streams during periods of drought In the basic academic education of their children; reading, writing and arithmetic, but they are not interested in knowing about another type of learning that happens in the classroom. A comprehensive health education program is an important part of the curriculum in most school districts. The goal of this education is not only to increase your child's knowledge about health and create positive attitudes towards their own well-being, but also to promote healthy behavior. By going beyond simply increasing knowledge, schools ask for more student participation than in many other subjects. Children are taught life skills, not just academic skills.